Maxillary second molar impaction in the adjacent ectopic third molar: Report of five rare cases - Bernardo Q Souki; Paula L Cheib; Gabriela M de Brito; Larissa S.M.C. Pinto (Wolters Kluwer Medknow Publications, 2015)
Maxillary second molar impaction in the adjacent ectopic third molar is a rare condition that practitioners might face in the field of pediatric dentistry and orthodontics. The early diagnosis and extraction of the adjacent ectopic third molar have been advocated, and prior research has reported a high rate of spontaneous eruption following third molar removal. However, some challenges in the daily practice are that the early diagnosis of this type of tooth impaction is difficult with conventional radiographic examination, and sometimes the early surgical removal of the maxillary third molar must be postponed because of the risks of damaging the second molar. The objective of this study is to report a case series of five young patients with maxillary second molar impaction and to discuss the difficulty of early diagnosis with the conventional radiographic examination, and unpredictability of self-correction.